FRAUD HEXAGON DALAM MENDETEKSI KECURANGAN LAPORAN KEUANGAN PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BEI PERIODE 2020 – 2024 - R Gina Aulia; Heliani (Universitas Sarjanawiyata Tamansiswa, 2026)
Fraudulent financial reporting in state-owned enterprises (SOEs) remains an important issue because it can be lower public trust and bring about considerable losses for the state. This study seeks to test how the ix elements of the Fraud Hexagon Theory are related to financial statement fraud in SOEs that were listed on the Indonesia Stock Exchange (IDX) throughout the 2020 – 2024 period. All SOEs listed on the IDX were tested as the population, and through purposive sampling the study obtained 50 observations drawn from 10 companies. The data were the processed using binary logistic regression with the help od SPSS version 31. The analysis reveals that, when each variable is tested individually, none of the independent variables is found to have a positive and significant effect on financial statement fraud. This results implies that the layered supervision carried out by the government and the State Audit Agency (BPK), together with compliance with regulations such as PMK No. 7/PMK.03/2015, PSAK No. 7, and SK-103/MBU/03/2021, has been effective enough to limit the likelihood of fraud in SOEs. The findings are expected to serve as a reference for company management in understanding the factors behind financial statement fraud, while also encouraging the strengthening of internal control systems so that preventive measures can be take earlier. Keywords: Fraud Hexagon, Financial Statement Fraud, SOEs